2021
DOI: 10.4236/jcc.2021.97006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Dedicated Slices of Different Configurations in 5G Core

Abstract: Network slicing is one of the most important concepts in 5G networks. It is enabled by the Network Function Virtualization (NFV) technology to allow a set of Virtual Network Functions (VNFs) to be interconnected to form a Network Service (NS). When network slices are created in 5G, some are shared among different 5G services while the others are dedicated to specific 5G services. The latter are called dedicated slices. Dedicated slices can be constructed with different configurations. In this research, dedicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
3
Order By: Relevance
“…The study carried out by Chai et al [6] implements a 5G testbed using open-source tools such as OpenStack [7], Tacker [8], and Free5GC [9]. The authors further evaluate the performance of three different deployment scenarios with multiple dedicated slices.…”
Section: A Implementation Of 5g Slicingmentioning
confidence: 99%
“…The study carried out by Chai et al [6] implements a 5G testbed using open-source tools such as OpenStack [7], Tacker [8], and Free5GC [9]. The authors further evaluate the performance of three different deployment scenarios with multiple dedicated slices.…”
Section: A Implementation Of 5g Slicingmentioning
confidence: 99%
“…O Free5GC implementa o núcleo da rede 5G, incluindo todos os elementos de rede (Network Elements -NE), e oferece suporte ao fatiamento de redes [5], [7], [16], conforme ilustrado na Figura 2. Por sua vez, o UERANSIM é um simulador de Rede de Acesso por Rádio (Radio Access Network -RAN) recomendado pelo Free5GC para criar uma simulação de rede 5G completa por software.…”
Section: Ambiente De Simulação De Rede 5gunclassified
“…Como resultado, concluímos que nossas propostas de NST fornecem um referencial técnico-teórico para a criação de NSTs para redes 5G, podendo nortear futuras pesquisas sobre novos modelos para novos cenários de uso do serviço. Dentre os trabalhos futuros, destacam-se a melhoria da simulação eMBB e a simulação dos cenários mMTC e URLLC [5], [17]. Para o cenário eMBB, é necessário aumentar a quantidade de UEs.…”
Section: Conclusõesunclassified
See 1 more Smart Citation
“…This isolation vs scalability trade-off has demonstrated that the most optimal solution is to provision 5GC slices with dedicated instances of UPF and SMF. This flavor, which corresponds to 5GC slice type B1 ( Figure 11 C), will satisfy the service requirements of most industry customers [ 47 , 48 ]. However, there also exist specific customers whose business requirements may make them ask operators for more tailored 5GC slices, such as type B2 slices ( Figure 11 D) and type B3 slices ( Figure 11 E).…”
Section: Cn Domainmentioning
confidence: 99%